Pelepasan lambat (slow release) diazinon dari mikrokapsul melamin urea formaldehid - Retno Sulistyo Dhamar Lestari; Rochmadi Rochmadi; Supranto Supranto (Jurnal Rekayasa Proses, 2013)
The basic concept of slow release is to control the active ingredient release from microcapsules by means of coating made from either water-insoluble, semi permeable or porous permeable materials. By designing microcapsules wall thickness, the diffusion rate of active ingredient can be controlled. Microcapsules containing diazinon pesticides as a core material have been prepared by in-situ polymerization using melamin urea formaldehyde prepolymer as the wall material. The polymerization had been done at 50 °C and pH 3, with homogenization time of 30 minutes, and microencapsulation time of 2 hours.To measure pesticide release rate, a number of Melamine Urea Formaldehyde (MUF) microcapsules were soaked in aquadest at various pH and microcapsules wall thicknesses. In this study, the diameter of MUF microcapsules ranged from 50 to 160 μm. Without surfactant addition, the microcapsule wall thickness was 13.8 μm, but by adding SDS and PVA the wall thickness of microcapsule decreased by 45% i.e. around 7.55 μm. For microcapsules with wall thickness of 13.8 μm, the pesticide releasing rate ranged from 0.52 x 10-6 to 1.69 x 10-6 mg/cm2·s. On the other side, the microcapsules with wall thickness of 7.55 μm the pesticide releasing rate dramatically increased by 74% ranged from 0.66 x 10-6 to 3.4 x 10-6 mg/cm2·s.